Scandinavian Olecranon Research in the Elderly (SCORE): protocol for a non- inferiority, randomised, controlled, multicentre trial comparing operative and conservative treatment of olecranon fractures in the elderly - Rantalaiho Ida; Laaksonen Inari; Launonen Antti P; Luokkala Toni; Flinkkilä Tapio; Salmela Mikko; Adolfsson L; Olsen Bo; Isotalo Kari; Ryösä Anssi; Äärimaa Ville; SCORE study group (BMJ PUBLISHING GROUP, 2022)
Introduction
The incidence of olecranon fractures is growing in the elderly population. The traditional operative approach is giving way among the elderly to conservative treatment, which seems to provide a comparable functional outcome with a lower complication burden. However, there is still a lack of reliable evidence to support this shift.The objective of this trial is to investigate whether conservative treatment of displaced olecranon fractures in patients aged 75 or older yields comparable results to those of operative treatment in terms of pain and daily function.
Methods and analysis
Scandinavian Olecranon Research in the Elderly (SCORE) is a randomised, controlled, multicentre, non-inferiority trial. Eligible patients will be randomised to either conservative or operative treatment. The sample size will be 68 patients and allocation done at a 1:1 ratio (34 patients per group). The randomisation is stratified according to the participating hospital and patient's sex. Both groups will receive the same postoperative physiotherapy and pain management. The primary outcome is Disabilities of the Arm, Shoulder and Hand at 1-year follow-up. Secondary outcomes are pain and satisfaction measured on visual analogue scales, Patient Reported Elbow Evaluation, range of motion of the elbow and extension strength of the elbow compared with the unaffected arm. Radiographs will be taken at each follow-up. Primary analysis of the results will be conducted on an intention-to-treat basis.
Ethics and dissemination
The study protocol for this clinical trial has been approved by the Ethics Committee of the Hospital District of Southwest Finland and will be submitted for approval to the Regional Ethics Committees in Linkoping, Sweden and Copenhagen, Denmark. Every recruiting centre will apply local research approvals. The results of this study will be submitted for publication in peer-reviewed journals.